PENYULUHAN KESEHATAN RUTIN PUSKESMAS UNTUK MENCEGAH SEKOLAH DASAR DENGAN KEJADIAN DBD DI KOTA MADIUN TAHUN 2017 - Puri Ratna Kartini; Santi Martini (Universitas PGRI Madiun, 2018)
Dengue Hemorrhagic Fever (DHF) is still a health problem in Madiun City. Based on data from the Madiun City Health Office (2011-2015) there has been a significant increase in DHF incidence over the past 5 years. Most DHF patients in Madiun City are elementary school children. This indicates that the program of DHF especially in primary school in Madiun is still less effective, especially routine health counseling by the heakth service centre related to PSN through 3M plus activities. This study aims to analyze the influence of routine health counseling by the health service centre to the incidence of DHF in Primary School in Madiun City. This research is an observational analytic research with case control design. The population in this study is divided into 2 groups, namely the case population (SD with DHF incidence) of 33 SD and control population (SD not with DHF incidence). The sample in this study is divided into 2 groups, namely the case sample (SD with selected DHF incidence) of 30 SD and control sample (SD not with DHF incidence) of 30 SD. Sampling technique is by Simple Random Sampling. From the result of the analysis test, it is found out that the routine health education of Puskesmas has an effect on the occurrence of DHF in Primary School in Madiun City (p = 0,001).